Expression of Language and Gender in the Movie “Imperfect: Karier, Cinta & Timbangan” (Sociolinguistic Studies) - Fauziyah Kurniawati (OKARA: Jurnal Bahasa dan Sastra, 2021)
The dialogues used by the male and female main character in the movie "Imperfect: Karier, Cinta & Timbangan" has many different language characteristics. This research aims to elaborate the expression of language characteristics of main male and female characters in the movie based on Qi Pan's theory and define the socio-cultural factors behind using these language characteristics. This research was qualitative descriptive research. The data source was the movie’s script of "Imperfect: Karier, Cinta & Timbangan." To collect data, the researcher used watching, listening, and writing techniques. Then, the data were analyzed using the textual analysis method. The results revealed that (a) the main female character uses 11 language characteristics according to Qi Pan's theory in dialogue. In contrast, the main male character does not use these language characteristics. Only hypercorrection characteristics are not used in both speeches, and (b) language differences in characters' speeches are influenced by socio-cultural factors that shape their personalities in the movie, creating gender stereotypes that appear in both genders based on their characters. This research represents an expression and relevance between language and gender, which can be found in real life and literary works, one of which is elaborated through Indonesian movie media.